The 10-month mortality rate among older patients treated for digestive system cancer during the first wave of the COVID-19 pandemic: The CADIGCOVAGE multicentre cohort study. Issue 2 (March 2023) - Aparicio, Thomas; Layese, Richard; Hemery, François; Tournigand, Christophe; Paillaud, Elena; De Angelis, Nicola; Quero, Laurent; Ganne, Nathalie; Prat, Fredéric; Pachev, Atanas; Galula, Gilles; Benderra, Marc-Antoine; et al.
Abstract: Introduction: The coronavirus disease 2019 (COVID-19) pandemic has had a dramatic impact on cancer diagnosis and care pathways. Here, we assessed the mid-term impact of the COVID-19 pandemic on older adults with cancer before, during and after the lockdown period in 2020. Materials and Methods: We performed a retrospective, observational, multicentre cohort study of prospectively collected electronic health records. All adults aged 65 or over and having been newly treated for a digestive system cancer in our institution between January 2018 until August 2020 were enrolled. Results: Data on 7, 881 patients were analyzed. Although the overall 10-month mortality rate was similar in 2020 vs. 2018–2019, the mortality rate among for patients newly treated in the 2020 post-lockdown period was (after four months of follow-up) significantly higher. A subgroup analysis revealed higher mortality rates for (i) patients diagnosed in the emergency department during the pre-lockdown period, (ii) patients with small intestine cancer newly treated during the post-lockdown period, and (iii) patients having undergone surgery with curative intent during the post-lockdown period. However, when considering individuals newly treated during the lockdown period, we observed lower mortality rates for (i) patients aged 80 and over, (ii) patients with a biliary or pancreatic cancer, and (iii) patients diagnosed in the emergency department. Discussion: There was no overall increase in mortality among patients newly treated in 2020 vs. 2018–2019. Longer follow-up is needed to assess the consequences of the pandemic. A subgroup analysis revealed significant intergroup differences in mortality.